Celiac plexus chemical neurolysis for refractory pain associated with superior mesenteric artery syndrome - Ravi Shankar Sharma; Ajit Kumar; Girish Kumar Singh; Sonal Goyal; Suyashi Sharma (Indian Journal of Pain, 2022)
Superior mesenteric artery (SMA) syndrome is caused by the compression of a part of the intestine between the aorta and SMA. It may lead to severe epigastric pain that is even refractory to conservative and surgical forms of therapy. Celiac plexus chemical neurolysis has been used in the past for debilitating pain associated with upper gastrointestinal malignancies and chronic pancreatitis. However, to date, this intervention has never been described in the literature for managing pain in SMA syndrome patients. Here, we describe the case of SMA syndrome whose pain was successfully managed with celiac plexus chemical neurolysis.